Deforestation offsets water balance changes due to climate variability in the Xingu River in eastern Amazonia - Panday, Prajjwal K.; Coe, Michael T.; Macedo, Marcia N.; Lefebvre, Paul; Castanho, Andrea D. de Almeida (Journal of hydrology (Amsterdam), 2015)
•We estimate changes to the water balance of Xingu due to climate variations and deforestation.•Climate effects have masked deforestation-induced changes to the water budget.•Water budget changes due to land use since the 1970s have thus far been modest.•Protected areas are critical in regulating the water cycle of the Xingu.•Continued deforestation could trigger significant changes in the water balance. Deforestation reduced forest cover in Brazil’s Xingu River Basin (XB; area: 510,000km2) from 90% of the basin in the 1970s to 75% in the 2000s. Such large-scale land cover changes can substantially alter regional water budgets, but their influence can be difficult to isolate from that of natural climate variability. In this study, we estimate changes to the XB water balance from the 1970s to the 2000s due to climate variations and deforestation, using a combination of long-term observations of rainfall and discharge; satellite-based estimates of evapotranspiration (MODIS) and surface water storage (GRACE); and numerical modeling estimates (IBIS) of water budget components (evapotranspiration, soil moisture, and discharge). Model simulations over this period suggest that climate variations alone accounted for a −82mm decrease (mean per unit area) in annual discharge (−14%, from 8190m3s−1 to 7806m3s−1), due to a −2% decrease in precipitation and +3% increase in evapotranspiration. Deforestation alone caused a +34mm increase in annual discharge (+6%), as a result of a −3% decrease in evapotranspiration and +1% increase in soil moisture across the XB. Climate variability and land cover change thus had opposite effects on the XB water balance, with climate effects masking deforestation-induced changes to the water budget. Protected areas, which cover 55% of the basin, have helped to mitigate the effects of past deforestation on water recycling in the Xingu. However, our results suggest that continued deforestation outside protected areas could trigger changes of sufficient magnitude to offset climate variability.